2006
DOI: 10.1111/j.1472-765x.2005.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase gene polymorphism of Staphylococcus aureus isolated from goat mastitis in Brazilian dairy herds

Abstract: Aims:  To investigate the coagulase gene polymorphism of Staphylococcus aureus isolated from mastitic goat's milk. Methods and Results:  A typing procedure based on coagulase gene polymorphism was used to discriminate S. aureus isolated from goat mastitis. Thirty‐six strains collected from goats belonging to herds from northern Ceara State and Serrana region of Rio de Janeiro State were analysed. Based on restriction fragment length polymorphism of 3′ end coagulase gene, the goat strains were grouped into 11 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 15 publications
3
30
1
4
Order By: Relevance
“…Of the 27 isolates of Staphylococcus, 2 (7.1%) were found to be producers of coagulase, the main virulence marker for the genus, which is associated with cases of infectious mastitis in milk cows SILVA, 2005). The results observed are consistent with those of other studies demonstrating that the family Muscidae is able to carry both coagulasepositive and -negative Staphylococcus species (BOUAMAMAA et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Of the 27 isolates of Staphylococcus, 2 (7.1%) were found to be producers of coagulase, the main virulence marker for the genus, which is associated with cases of infectious mastitis in milk cows SILVA, 2005). The results observed are consistent with those of other studies demonstrating that the family Muscidae is able to carry both coagulasepositive and -negative Staphylococcus species (BOUAMAMAA et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…A caracterização fenotípica foi realizada por meio de testes de triagem que incluíram a morfologia macroscópica e microscó-pica, testes de catalase, oxidase, coagulase e produção de acetoína (teste de Voges Proskauer), realizados e interpretados segundo o National Mastitis Council (NMC, 2004). Isolados fenotipicamente identificados como S. aureus foram submetidos à identificação genotípica por meio da Reação em Cadeia da Polimerase (PCR) espécie-específica para o gene femA de S. aureus, de acordo com Silva;Silva (2005).…”
Section: Introductionunclassified
“…They determined that coagulase gene polymorphism of S. aureus isolates from mastitic cow milk by RFLP method using AluI enzyme produced 9 different genotype strains. Rodrigues da Silva and Silva [22] , reported that there were 49 different types of RFLP samples after digestion with AluI enzyme. Raimundo et al [23] examined coa gene type of 151 samples of cattle S. aureus isolates from 76 farms I II III IV I II III IV I II III IV I II III IV P 6 33 by using Coag2 and Coag3 primers and found 6 types of PCR.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that both counts and localisations of AluI restriction regions in 3'ends of gene coagulase contain a sequence of 81 base pairs which is different between S. aureus isolates [18] . The classification of S. aureus isolates depending on gene coa is a simple method for molecular typing and can be assumed as a validation test [18,22] . Aslantas et al [9] reported that RFLP models of gene coagulase of S. aureus isolates from cattle mastitis showed a great diversity.…”
Section: Discussionmentioning
confidence: 99%